Burma file a question of democracy - Soe Myint 1967- (Politics & international relations, 2004)
This compilation of reports and feature stories from correspondents of Mizzima News and Feature Service addresses the struggle of the country of Burma and its citizens living under a military regime. These collected stories combine to create a timely introduction to Burma's current political situation. Topics addressed include Burma's relations with its neighbors, domestic affairs, and Burmese refuges in India.